1975
DOI: 10.1159/000162793
|View full text |Cite
|
Sign up to set email alerts
|

Beitrag zur Morphologie der myometrialen und dezidualen Arterien bei normalen Schwangerschaften, EPH-Gestosen und mütterlichem Diabetes mellitus

Abstract: 127 specimens, obtained by different methods from the myometrium and the placental bed after parturition, are investigated histologically. This material includes normal pregnancies as well as cases of maternal diabetes with and without hypertension and cases of hypertension in EPH-gestosis. The different parts of the arterial system (spiral arteries, basal arteries, radial arteries) are separately investigated. Physiologically, the pregnancy induces changes in the wall of the decidual arteries and possibly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Uteroplacental blood flow and pre-eclampsia In diabetes changes of the trophoblasts of the placenta (Jones & Fox 1976), villous structure (Björk & Persson 1984) and narrowing of the lumen of the arteriolae in the placental bed (Emmerich et al 1975) have been observed. Thus, there is a histological basis for alterations in the uteroplacental blood flow in diabetic pregnancy.…”
Section: Hydramniosmentioning
confidence: 99%
“…Uteroplacental blood flow and pre-eclampsia In diabetes changes of the trophoblasts of the placenta (Jones & Fox 1976), villous structure (Björk & Persson 1984) and narrowing of the lumen of the arteriolae in the placental bed (Emmerich et al 1975) have been observed. Thus, there is a histological basis for alterations in the uteroplacental blood flow in diabetic pregnancy.…”
Section: Hydramniosmentioning
confidence: 99%